2010
DOI: 10.1080/02672571003780106
|View full text |Cite
|
Sign up to set email alerts
|

A journey to the authentic: Museum visitors and their negotiation of the inauthentic

Abstract: This qualitative research was set within a literary heritage museum replete with replica artefacts. We explored how the inauthentic is negotiated in this context and examined the outcomes of these negotiations. Our research revealed that scene setting, freedom, and imagination contribute to visitors' potential to overcome the absence of indexically authentic artefacts, and we identified a role for existential authenticity in this process. We make three key contributions to marketing theory on authenticity: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…From a marketing perspective, this presents significant challenges of branding, distribution, promotion and customer service (Walmsley 2010). But on the positive side, it means that these companies meet their audiences on the audience's terms and in familiar surroundings, circumventing the widely acknowledged barrier to attendance of arts venues intimidating new and unfamiliar customers (Kotler and Scheff 1997) and reducing the risk of dissonance (Hede and Thyne 2010). The analysis of the audience reactions to National Theatre of Scotland's rural touring revealed the tangible value that touring productions can bring to rural communities and indicated that arts organizations and their marketers can indeed be perceived as value creators if the marketing mix is right.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a marketing perspective, this presents significant challenges of branding, distribution, promotion and customer service (Walmsley 2010). But on the positive side, it means that these companies meet their audiences on the audience's terms and in familiar surroundings, circumventing the widely acknowledged barrier to attendance of arts venues intimidating new and unfamiliar customers (Kotler and Scheff 1997) and reducing the risk of dissonance (Hede and Thyne 2010). The analysis of the audience reactions to National Theatre of Scotland's rural touring revealed the tangible value that touring productions can bring to rural communities and indicated that arts organizations and their marketers can indeed be perceived as value creators if the marketing mix is right.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their qualitative study of museum visitors negotiating replica artefacts, Hede and Thyne (2010) call on cultural organizations to consider the role of authenticity in consumption situations to mitigate against consumer dissonance. They advocate the use of scene setting to authenticate the consumer experience and suggest that this can be enhanced through freedom and imagination.…”
Section: Engaging With Rural Audiencesmentioning
confidence: 99%
“…These are presented in Table 1. <Insert Table 1: "Trustworthiness of the study and findings (modelled on Hede & Thyne, 2010)" about here> Table 2 provides the profiles of the research participants. As can be seen from Table 2, the research participants were diverse in terms of their cultural backgrounds, demographic profiles and had sufficient experience as expert informants.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…We used the nine evaluative criteria for the trustworthiness of the study and its findings, which social researchers have suggested to consider when undertaking interpretative research (Hede & Thyne, 2010, Flint, Woodruff, & Gardial, 2002Lincoln & Guba, 1985;Strauss & Corbin, 1990). These are presented in Table 1. <Insert Table 1: "Trustworthiness of the study and findings (modelled on Hede & Thyne, 2010)" about here> Table 2 provides the profiles of the research participants.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…But heritage sites are also spaces of abstraction, created to provide performed versions of the past. Museographic display, textual information and communication strategies are used as compensating factors for the gap between "reality", or the original context, and the synthesis of its representation (Hede & Thyne, 2010;Olick, Vinitzky-Seroussi, & Levy, 2011).…”
Section: Cultural and Heritage Tourismmentioning
confidence: 99%